A descriptive analysis of self‐injury in community settings: exploring behaviour–behaviour contingencies. Issue 12 (14th March 2018) - Courtemanche, A. B.; Lloyd, B. P.; Tapp, J. T.
Abstract: Background: Self‐injurious behaviour (SIB) is a treatment‐resistant aberrant behaviour that significantly impacts the lives of people with intellectual disabilities (ID). Direct observations of SIB under naturally occurring conditions can inform the unique structural properties of these behaviours, and the contexts in which they occur. While previous applications of sequential analyses have identified strong temporal associations between instances of SIB, they have relied on methods that do not adequately control for chance sequencing and may mask within‐participant variability by pooling data across contexts and response topographies. We applied a new sequential analysis method to quantify SIB–SIB contingencies within and across topographies for individuals with ID in community settings. We also explored the extent to which the direction and strength of SIB–SIB contingencies varied by context. Method: Seven individuals with chronic SIB were video‐recorded during their daily routines. A continuous, timed‐event data collection system was used to measure frequencies of five topographies of SIB and duration of staff interactions. We used an event lag with pauses sequential analysis method to estimate SIB–SIB contingencies within and across topographies and during times with and without staff interaction. Results: Positive SIB–SIB contingencies were identified for all participants, with contingency strengths varying among participants and topographies. The strength and direction of the SIB–SIB contingencies also varied by the presence and absence of staff interaction. Conclusions: Our results suggest the direction and strength of SIB–SIB contingencies may be fluid based on the presence or absence of certain environmental context variables. Evaluating SIB–SIB contingencies under different environmental conditions may help identify contexts in which SIB is likely to persist.